Chicken meat quality as a function of fasting period and water spray - Komiyama, C M [UNESP]; Mendes, Ariel Antonio [UNESP]; Takahashi, S E [UNESP]; Moreira, J; Garcia, R G; Sanfelice, C [UNESP]; Borba, H S [UNESP]; Leonel, F R [UNESP]; Paz, Ibiara Correia de Lima Almeida [UNESP]; Balog, A [UNESP] (Fundação APINCO de Ciência e Tecnologia Avícolas, 2008)
This study aimed at evaluating the effect of different fasting periods and water spray during lairage on the quality of chicken meat. A number of 300 male Ross broilers were reared up to 42 days of age, and submitted to four pre-slaughter fasting periods (4, 8, 12, and 16 hours) and sprayed with water or not during lairage. Deboned breast meat was submitted to the following analysis: pH, color, drip loss, water retention capacity, cooking loss, and shear force. There was a significant effect (p < 0.05) of fasting period on meat luminosity was significantly different, with the highest value obtained for 4-hour fasting, whereas no difference was found among the other fasting periods. Meat pH values were different among fasting periods when birds received water spray, with birds fasted for 4, 8, and 12 hours of fasting presenting lower meat pH values (5.87, 5.87, and 6.04, respectively). The interaction between fasting period and water spray influenced meat drip loss and cooking loss, with birds fasted for 16h and not receiving water spray presenting higher drip loss (4.88) and higher cooking loss (28.24) as compared to the other birds. Fasting period affects meat quality, and very short periods (4h) impair meat quality.
Keywords: Broilers; color; meat; pH